Technology transfer: Making the most of your intellectual property - Neil F Sullivan (1959- (Cambridge Univ, 1995)
The book is a careful account of how to start the process of commercialisation of technology, and describes in detail the difficulties and the amount of time needed to carry the process through to a successful conclusion. It provides a much needed step by step guide to the commercialisation of research. It addresses three major themes: how to protect your intellectual property; how to develop it commercially via licensing and business 'start up'; and how to finance and management your nwe company